Implications the Role of miR-155 in the Pathogenesis of Autoimmune Diseases - Pashangzadeh, Salar; Motallebnezhad, Morteza; Vafashoar, Fatemeh; Khalvandi, Azadeh; Mojtabavi, Nazanin (Frontiers in Immunology, 2021)
MicroRNAs (miRNAs) are small noncoding conserved RNAs containing 19 to 24 nucleotides that are regulators of post-translational modifications and are involved in the majority of biological processes such as immune homeostasis, T helper cell differentiation, central and peripheral tolerance, and immune cell development. Autoimmune diseases are characterized by immune system dysregulation, which ultimately leads to destructive responses to self-antigens. A large body of literature suggests that autoimmune diseases and immune dysregulation are associated with different miRNA expression changes in the target cells and tissues of adaptive or innate immunity. miR-155 is identified as a critical modulator of immune responses. Recently conducted studies on the expression profile of miR-155 suggest that the altered expression and function of miR-155 can mediate vulnerability to autoimmune diseases and cause significant dysfunction of the immune system.